2016
DOI: 10.3847/0067-0049/227/2/17
|View full text |Cite
|
Sign up to set email alerts
|

Linear Polarization of Class I Methanol Masers in Massive Star-Forming Regions

Abstract: Class I methanol masers are found to be good tracers of the interaction between outflows from massive young stellar objects with their surrounding media. Although polarization observations of Class II methanol masers have been able to provide information about magnetic fields close to the central (proto)stars, polarization observations of Class I methanol masers are rare, especially at 44 and 95 GHz. We present the results of linear polarization observations of 39 Class I methanol maser sources at 44 and 95 GH… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 50 publications
1
16
1
Order By: Relevance
“…Wiebe & Watson (1998) found that in masers with strong linear polarization, changes in the orientation of the magnetic field along the line of sight could cause rotation of the linear polarization vector to produce circular polarization. Observing with the Korean VLBI network telescopes in single dish mode, Kang et al (2016) measured (2.0±0.2) % linear polarization in the 44 GHz CH 3 OH masers toward DR21W. Given this low value, it is unlikely that linear polarization is causing the observed Stokes V in our observations.…”
Section: Discussionmentioning
confidence: 62%
“…Wiebe & Watson (1998) found that in masers with strong linear polarization, changes in the orientation of the magnetic field along the line of sight could cause rotation of the linear polarization vector to produce circular polarization. Observing with the Korean VLBI network telescopes in single dish mode, Kang et al (2016) measured (2.0±0.2) % linear polarization in the 44 GHz CH 3 OH masers toward DR21W. Given this low value, it is unlikely that linear polarization is causing the observed Stokes V in our observations.…”
Section: Discussionmentioning
confidence: 62%
“…They argue that the masers are unsaturated and that the theory of Nedoluha and Watson (1992) applies; specifically that the linear polarization arises from anisotropic pumping and anisotropic radiation losses and the circular polarization from non-Zeeman effects (Watson, 2009). Kang et al (2016) present a survey of linear polarization in 44 GHz and 95 GHz Class I masers conducted with a single dish from the Korean VLBI Network (KVN). Their results yielded a lower fractional linear polarization and they argue accordingly for a diminished influence of anisotropic pumping and losses than Wiesemeyer et al (2004).…”
Section: Ghz and 44 Ghz Methanol Masersmentioning
confidence: 99%
“…There remain broad open questions in both the micophysics and macrophysics of star formation theory (McKee and Ostriker, 2007). Maser polarization observations in SFR probe the fine-scale magnetic field in dense regions n ∼ 10 5−11 cm −3 of obscured HMSFR (Kang et al, 2016) and therefore provide constraints on the theory of high-mass as opposed to low-mass star formation (Zinnecker and Yorke, 2007). In addition, masers are confined to certain evolutionary phases of HMSF, specifically between the formation of hot dense molecular cores (HDMC) (Zinnecker and Yorke, 2007), equivalently highmass protostellar objects (HMPO) (McKee and Ostriker, 2007), and their subsequent evolution into ultra-compact HII regions (UCHII) (Churchwell, 2002).…”
Section: Relationship Of Maser Polarization Observations To Star Formmentioning
confidence: 99%
“…In this paper, we report on single-dish measurements of linear polarisation toward 44 and 95 GHz methanol maser sources. The full results are published in Kang et al (2016). We also report on the preliminary results of follow-up VLBI observations, especially on the G10.34-0.14.…”
Section: Introductionmentioning
confidence: 97%